Iron chelation as a therapeutic target in vanadium neurotoxicity and Parkinson's disease: role of medicinal plants - Olaolorun, Francis; Howes, Melanie-Jayne R.; Elufioye, Taiwo; Odeku, Oluwatoyin A.; Olopade, James; Chazot, Paul (Frontiers in Neurology, 2025)
Bioprospecting plant natural products has yielded significant success in the development of symptomatic treatment of neurodegenerative diseases, including the two most common, Alzheimer's and Parkinson's diseases (PD). Dysregulation of iron has been strongly implicated in the pathophysiology of these serious intractable diseases. A series of Nigerian endemic plants' methanolic extracts were explored using a Ferrozine binding iron chelation assay. This identified Spondias purpurea L. (SP) leaves as a potential therapeutic candidate and this was determined by evaluation of oxidative stress in 6-hydroxydopamine (6-OHDA)-exposed monoamine cell culture and Drosophila models of PD and vanadium neurotoxicity. SP treatment protected CAD cells against 6-OHDA toxicity and improved survival in PINK-1 mutant flies, though it had little effect on motor deficits. Furthermore, SP treatment reduced the vanadium-induced reactive oxygen species, and notably, staggered SP treatment significantly extended lifespan in vanadium-treated flies. Overall, Spondias purpurea L. leaf methanolic extract exhibited iron-chelating, antioxidant, neuroprotective, and life-extending properties, relevant to Parkinson's disease and vanadium-induced toxicity.